2006
DOI: 10.3892/ijo.28.5.1021
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine, an unexpected anti-tumor agent, and its potential for the treatment of glioblastoma (review)

Abstract: Abstract. Cimetidine (CIM), the prototypical histamine H2 receptor antagonist (H2RA), was brought to market based on its ability to accelerate healing of gastrointestinal ulcers through the inhibition of gastric acid secretion. Cimetidine, the most studied H2RA, has been demonstrated to possess anti-tumor activity against colon, gastric and kidney cancers, and melanomas. This activity involves a number of different mechanisms of action: a) CIM antagonizes tumor cellmediated interleukin-1-induced activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 96 publications
(149 reference statements)
1
42
0
Order By: Relevance
“…Cimetidine has been demonstrated to possess anti-tumor activity against colon, gastric, and kidney cancers and melanomas. This activity involves a number of different mechanisms of action, including blocking the cell growth-promoting activity of histamine (Lefranc et al, 2006). With respect to GBM, cimetidine combined with temozolomide was superior to temozolomide alone in extending the survival of nude mice with human GBM cells orthotopically xenografted into their brain (Lefranc et al, 2005).…”
Section: Cimetidinementioning
confidence: 99%
“…Cimetidine has been demonstrated to possess anti-tumor activity against colon, gastric, and kidney cancers and melanomas. This activity involves a number of different mechanisms of action, including blocking the cell growth-promoting activity of histamine (Lefranc et al, 2006). With respect to GBM, cimetidine combined with temozolomide was superior to temozolomide alone in extending the survival of nude mice with human GBM cells orthotopically xenografted into their brain (Lefranc et al, 2005).…”
Section: Cimetidinementioning
confidence: 99%
“…Since that time, several studies have reported survival advantages with cimetidine treatment, mainly in patients with gastrointestinal cancer (11)(12)(13)(14). Further, positive effects have also been demonstrated in non-gastrointestinal cancer patients, such as those with renal cell carcinoma (15), malignant melanoma (16) and glioblastoma (17).…”
Section: Introductionmentioning
confidence: 99%
“…( [15][16][17][18][19][20][21] Of note is the fact that all three drugs have shown anti-angiogenic activity. We have recently reported three cases in which favorable responses to a combination treatment comprising cimetidine, COX-2 inhibitor and RAS inhibitor in mRCC were observed with a relatively long duration of the effects, at least 1 year of time to progression.…”
mentioning
confidence: 99%
“…Recently, two phase-III trials (13,14) have shown improved PFS and increased objective response rate (ORR) with bevacizumab plus IFN-a, when compared with IFN-a alone, as first-line treatment. The combination of IFN-a plus bevacizumab has now become one of the standard first-line treatments for favorable-to intermediate-risk mRCC patients.The antitumor effects of cimetidine, cyclooxygenase-2 (COX-2) inhibitor and renin-angiotensin-system (RAS) inhibitor (angiotensin-converting-enzyme [ACE] inhibitor or angiotensin-II type-1 receptor [AT1R] antagonist) have been recognized in previous studies.( [15][16][17][18][19][20][21] Of note is the fact that all three drugs have shown anti-angiogenic activity. We have recently reported three cases in which favorable responses to a combination treatment comprising cimetidine, COX-2 inhibitor and RAS inhibitor in mRCC were observed with a relatively long duration of the effects, at least 1 year of time to progression.…”
mentioning
confidence: 99%